2009
DOI: 10.1186/1475-2875-8-99
|View full text |Cite
|
Sign up to set email alerts
|

PfeIK1, a eukaryotic initiation factor 2α kinase of the human malaria parasite Plasmodium falciparum, regulates stress-response to amino-acid starvation

Abstract: Background: Post-transcriptional control of gene expression is suspected to play an important role in malaria parasites. In yeast and metazoans, part of the stress response is mediated through phosphorylation of eukaryotic translation initiation factor 2α (eIF2α), which results in the selective translation of mRNAs encoding stress-response proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 44 publications
3
97
0
11
Order By: Relevance
“…For example, a GCN2-like kinase has been identified that is also present in A. locustae, another insect microsporidia. GCN2p is involved in eiF2α phosphorylation, leading to translation inhibition in nutrient starvation conditions in yeast 39 as well as in other intracellular eukaryotic parasites [40][41][42] . Furthermore, Ste20 and Ste11 belonging to the MAPKKK pathway were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a GCN2-like kinase has been identified that is also present in A. locustae, another insect microsporidia. GCN2p is involved in eiF2α phosphorylation, leading to translation inhibition in nutrient starvation conditions in yeast 39 as well as in other intracellular eukaryotic parasites [40][41][42] . Furthermore, Ste20 and Ste11 belonging to the MAPKKK pathway were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…This approach culminated in a kinome-wide study demonstrating that 23 P. berghei ePKs are redundant for asexual erythrocytic parasite development in mice and identifying phenotypes in sexual development for a number of these 23 ePKs [51]. A similar strategy in P. falciparum identified roles for an orphan kinase in proliferation rate linked to the number of progeny merozoites per schizont [36], for an eIF2a kinase in response to starvation stress, similar to GCN2, its closest homologue in yeast [52], and for CDPKs in motility during invasion [53] or egress of merozoites from the erythrocyte [54], to cite a few specific studies; more recently, a kinome-wide approach [19] identified 36 ePKs as refractory to gene disruption, and thus as likely crucial players in asexual proliferation in erythrocytes.…”
Section: E C To C a R P U S S Il Ic U Lo S U S T H A L A S S I O S I mentioning
confidence: 99%
“…In P. falciparum, exposure to amino acid-free RPMI results in the phosphorylation of parasite eIF2α (PfeIF2α) (15). Considering that isoleucine is the only amino acid for which the parasite can truly be starved, we examined the specificity of this response.…”
Section: Isoleucine-starved Parasites Have Reduced Levels Of Central-mentioning
confidence: 99%
“…Plasmodium does not have a TOR complex (14) and lacks the downstream transcription factors and biosynthetic pathways that mediate GCN2 action. An ortholog of eIF2α and three putative eIF2α kinases have been identified previously in the P. falciparum genome (15)(16)(17). One of them, PfeIK2, controls latency in sporozoite development in the mosquito (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation